Climate Change and Shifts in Migratory Bird Patterns: Evidence from Citizen Science Data in eBird - Ashra Khadim Hussain; Moazzam Rafiq Khan (International Journal of Applied Research and Innovation, 2026)
Climate change is increasingly recognized as a major driver of change in migratory bird behavior, yet comprehensive empirical assessments across broad spatial and temporal scales remain limited. This study examines how climate change influences migratory bird patterns using large-scale citizen science data from the eBird platform. By analyzing temporal shifts in migration phenology, spatial redistribution across latitudinal and elevational gradients, and implications for ecological forecasting, the study provides an integrated perspective on climate-driven migration dynamics. Results indicate consistent advancement of migration timing, increased variability in seasonal movements, and widespread redistribution of migratory routes and seasonal ranges. These patterns align with long-term warming trends, altered climatic extremes, and changing habitat suitability, and are supported by convergence with independent monitoring and modeling studies. The findings demonstrate that eBird data reliably capture complex migratory responses to climate change while offering critical insights for adaptive conservation strategies. Integrating participatory science into migration research enhances the capacity to detect early warning signals, refine predictive models, and inform cross-scale conservation planning under rapidly changing environmental conditions.